2019
DOI: 10.1088/1475-7516/2019/11/048
|View full text |Cite
|
Sign up to set email alerts
|

Cosmic ray small-scale anisotropies in quasi-linear theory

Abstract: The distribution of arrival directions of cosmic rays is remarkably isotropic,

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…We follow the steps outlined in Ref. [6]. For further details we refer to this paper and references therein.…”
Section: Analytical Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…We follow the steps outlined in Ref. [6]. For further details we refer to this paper and references therein.…”
Section: Analytical Calculationmentioning
confidence: 99%
“…The authors of Ref. [6] take into account these correlations and put forward a model to predict the APS based on a perturbative expansion of the time-evolution operator. However, a rather unrealistic white-noise power spectrum of turbulence was adopted to allow for some explicit analytical results.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, one can only hope to predict statistical moments of the phase space density for a statistical ensemble of turbulent magnetic fields. Traditionally, one is mostly interested in the first moment, the ensemble average, though see Mertsch and Ahlers (2019) for the computation of a second-order moment.…”
Section: Derivation Of the Fokker-planck Equationmentioning
confidence: 99%
“…There are however situations where even Galactic transport is not diffusive or where the diffusive picture is questionable. These include the escape of Galactic CRs from the CR halo around the knee (DeMarco et al 2007;Giacinti et al 2015), near source transport Kachelrieß et al 2015), stochastic acceleration (O'Sullivan et al 2009;Winchen and Buitink 2018), also in relativistic turbulence (Demidem et al 2019), and the study of CR anisotropies Schwadron et al 2014;Mertsch and Funk 2015;Ahlers and Mertsch 2015;López-Barquero et al 2016;Pohl and Rettig 2016;Kumar et al 2019;Mertsch and Ahlers 2019). In the following, we will briefly review the use of test particle simulations and discuss the results for a few physics cases.…”
Section: Applicationsmentioning
confidence: 99%
“…Interestingly, it has been suggested that the turbulent Galactic magnetic field could be the source of small-scale anisotropies Ahlers 2014;Ahlers & Mertsch 2015;Battaner et al 2015;López-Barquero et al 2016;Mertsch & Ahlers 2019). This idea has been investigated using test particle simulations of CRs in synthetic turbulence where sky maps of the CR arrival directions can be obtained from the phase-space density back-tracked along the CR trajectories to an earlier time (see Ahlers & Mertsch 2017 for a review).…”
Section: Introductionmentioning
confidence: 99%